Leg stiffness and mechanical energetic processes during jumping on a sprung surface - Arampatzis, A.; Brüggemann, G. P.; Morey Klapsing, G. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The purposes of this study were: a) to examine the effect of verbal instructions given to the subjects on the control of lower extremity stiffness and b) to determine the effect of leg stiffness on mechanical energetic processes during drop jumps on a sprung surface. Methods: A total of 10 female athletes performed a series of drop jumps on a sprung surface from heights of 20 and 40 cm. The instructions given to the subjects were a) "jump as high as you can" and b) "jump high a little faster than at your previous jump." The jumps were performed at each height until the athlete could not achieve a shorter ground contact time. Four jumps per subject per height were analyzed. The ground reaction forces were measured using a "Kistler" force plate (1000 Hz). The athletes' body positions were recorded using a high-speed (250 Hz) video camera. The deformation of the sprung surface was determined by another high-speed camera operating at 500 Hz. Surface EMG was used to measure muscle activity in five leg muscles. Results: The contact time showed high correlation with leg stiffness as well as with ankle and knee stiffness. The change in leg stiffness was not due to the duration of the preactivation but rather to the level of activation during this phase. An increase in leg stiffness caused an increase in the energy stored and recovered in and by the sprung surface and a decrease of the energy produced by the subjects. Conclusions: By influencing contact time through verbal instructions, it is possible to control leg stiffness. Maximal vertical take-off velocity of the center of mass and maximal take-off body energy can be achieved having different levels of leg stiffness. The maximization of mechanical power is achieved by optimal leg stiffness values and leg muscle preactivation levels.